(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
In this paper, a Microgrid has been developed consist of renewable energy resources in MATLAB Simulink environment. First, a DVR has been modeled and used in the developed microgrid model. Power quality analysis is carried out with the help of simulation results considering the effect of Dynamic Voltage Restorer (DVR). Also, a MATLAB Simulink model of the DSTATCOM has been developed to compare its performance with DVR. The same DSTATCOM has been used with the earlier developed microgrid model to test its effectiveness. The performance of both DVR and DSTATCOM has been compared in common scenarios related to power quality issues and results are analyzed.